2010
DOI: 10.1128/jvi.01316-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of AKT Kinase in Measles Virus Replication

Abstract: Many RNA and DNA viruses activate serine-threonine kinase AKT to increase virus replication. In contrast, measles virus (MV) infection leads to downregulation of AKT. This is thought to be beneficial for the virus because it correlates with immune suppression. To determine whether this is a sacrifice for the virus, we used a recombinant virus and transfected cells expressing constitutively active AKT and evaluated its effect on virus replication. In vitro, overexpression of AKT did not influence virus replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In contrast to examples of viral exploitation of the Akt pathway (3,8,13), a decrease in polymerase activity could indicate that Akt phosphorylation of the NoV RdRp is an antiviral strategy protecting the infected cell. However, this idea may be hard to reconcile with our observation that the Akt phosphorylation event occurs in the most epidemiologically fit genotype (GII.4) and is generally absent from others.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to examples of viral exploitation of the Akt pathway (3,8,13), a decrease in polymerase activity could indicate that Akt phosphorylation of the NoV RdRp is an antiviral strategy protecting the infected cell. However, this idea may be hard to reconcile with our observation that the Akt phosphorylation event occurs in the most epidemiologically fit genotype (GII.4) and is generally absent from others.…”
mentioning
confidence: 96%
“…Alternatively, not all viruses activate the PI3K/Akt pathway. For example, with measles virus, infection leads to a downregulation of Akt that appears to play a role in immune suppression (8).…”
mentioning
confidence: 99%
“…The phosphorylation of both viral and cellular proteins have been shown to play a major role in the life cycle of numerous viruses, many of which exploit critical cellular signaling pathways through the selective activation of cellular phosphatases and kinases 16,31,31,42 . Targeting key regulators of these signaling pathways, such as PP1, holds broad application potential as PP1 regulates an enormous number of cellular functions and is highly conserved among eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that PP1 plays a prominent role in viral replication affecting the antiviral response, signal transduction, cell cycle checkpoint control, RNA splicing, and protein synthesis 11–15 . While the significance of cellular kinases for RVFV has been partially described 1619 , relatively little is known about the impact of cellular phosphatases on viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…As yet, MV is the only pathogen known to interfere with the activation of this pathway in a contact-dependent manner. This pathway is, however, often activated by viruses because it supports their replication directly or by promoting host cell survival and cell cycle entry [99][100][101][102], yet Akt kinase activation apparently has no impact on replication of an attenuated MV strain in Jurkat T cells [103].…”
Section: Signaling Pathways Targeted By MVmentioning
confidence: 99%